Political Economy Analysis of Media in Reporting Sesingal Tidung on Radio Republik Indonesia, Tarakan City - Rahmadhani, Adinda; Nurliah, Nurliah; Purwanti, Silviana; Muhammad, Harry Isra (Jurnal Indonesia Sosial Sains, 2026)
This study examines the political economy of media representation, focusing on the coverage of Sesingal Tidung culture in Radio Republik Indonesia (RRI) Tarakan. Utilizing Vincent Mosco's media political economy theory, the research explores the commodification, spatialization, and structuration processes that shape how local culture is portrayed. The study highlights the challenges in preserving cultural identity amidst the pressures of commercialization and government policies. It finds that media coverage, while promoting economic potential, often undermines the authenticity of cultural expressions. This research contributes to understanding how media both reflects and influences the political and economic dynamics surrounding cultural preservation in the globalized media landscape.